2013
DOI: 10.3390/molecules18089132
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Oil Palm Mesocarp Fiber Characteristics Using Superheated Steam Treatment

Abstract: Abstract:In this study, oil palm mesocarp fiber (OPMF) was treated with superheated steam (SHS) in order to modify its characteristics for biocomposite applications. Treatment was conducted at temperatures 190-230 °C for 1, 2 and 3 h. SHS-treated OPMF was evaluated for its chemical composition, thermal stability, morphology and crystallinity. OPMF treated at 230 °C exhibited lower hemicellulose content (9%) compared to the OPEN ACCESSMolecules 2013, 18 9133 untreated OPMF (33%). Improved thermal stability of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
85
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 30 publications
(44 reference statements)
14
85
0
4
Order By: Relevance
“…Therefore, modification is needed to improve fiber/matrix adhesion. Recently, modification of OPMF by superheated steam (Nordin et al 2013), alkaline peroxide , or silane coupling agents (Eng et al 2014b) was successfully conducted by our research group. Huda et al (2008) modified kenaf fibers using alkalization and silane treatments and then blended them with polylactic acid (PLA).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, modification is needed to improve fiber/matrix adhesion. Recently, modification of OPMF by superheated steam (Nordin et al 2013), alkaline peroxide , or silane coupling agents (Eng et al 2014b) was successfully conducted by our research group. Huda et al (2008) modified kenaf fibers using alkalization and silane treatments and then blended them with polylactic acid (PLA).…”
Section: Introductionmentioning
confidence: 99%
“…The OPF was first shredded and then pressed to remove the juice as described by Abdullah et al (2015). Raw OPMF, OPEFB, and OPF were prepared as described by Nordin et al (2013). The size of each fiber was about 8 cm to 10 cm in length, and there was no further mechanical treatment prior to the SHS treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The use of superheated steam (SHS) for surface modification has been recently reported, and it was shown that SHS treatment altered the properties of OPMF (Nordin et al 2013;Then et al 2014), OPEFB (Bahrin et al 2012), and OPF (Karuppuchamy et al 2015) by selective removal of hemicellulose. Moreover, the treatment resulted in the removal of silica bodies from the surface of fibers and an increase in fiber thermal stability and the removal of moisture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Char produced via pyrolysis of MF at 450 -800 o C and 3.5 h retention time exhibit prominent fixed carbon content and significantly less ash content [12]. In addition, MF has been reported to be suitable for all oil palm wastes applications because it comprises of fruit fibre, crushed kernels and shells [13]. It was found by [14] that PKS pyrolyzed at 750 o C, with heating rate of 10 o C/min and residence time of 1 h yielded extremely potential bio-char for carbon fuel utilization.…”
Section: Introductionmentioning
confidence: 99%